Diagnosis dan tatalaksana nyeri pada rongga mulut yang disebabkan oleh infeksi virus herpes Diagnosis and management of pain in oral cavity caused by herpes virus infection - Erni Marlina; Ali Yusran; Zohra Nazaruddin (Journal of Dentomaxillofacial Science, 2012)
There are 80 types of known herpes virus, 8 of them can cause infection on humans. They are herpes simplex virus(HSV) 1 and 2, varicella zoster virus (VZV), cytomegalovirus, Epstein-Barr virus, human herpes virus (HHV6) Aand B, and paramyxovirus. HSV1, HSV2, and VZV are the virus known to cause oral mucosal diseases. This paperaims to review and discuss orofacial pain caused by herpes virus infection. Detail anamnesis about prodromal signand symptom with clinical features that vesicles, labial and intraoral lesions, and unilateral distribution of lesionsare characterized oral herpes virus infections. It can be concluded that detailed anamnesis and an understandingabout oral clinical sign and symptom may confirm diagnosis of herpes virus infections.